2020
DOI: 10.1007/s11606-020-06234-x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity Management in Black Women Diagnosed with Breast Cancer: the Role of Primary Care in Shared Care

Abstract: BACKGROUND: Black women are more likely to have comorbidity at breast cancer diagnosis compared with White women, which may account for half of the Black-White survivor disparity. Comprehensive disease management requires a coordinated team of healthcare professionals including primary care practitioners, but few studies have examined shared care in the management of comorbidities during cancer care, especially among racial/ethnic minorities. OBJECTIVE: To examine whether the type of medical team composition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…36 Previous studies have shown that health-related outcomes, including chronic disease management and survival, are better when primary care is integrated as part of the care team. 37-41 In our study, it was encouraging that primary care was included in the clinical MTS for almost 74% of cancer patients. We also identified 16.7% lower incidence of high-complexity MTS care among patients with colorectal cancer compared with patients with breast cancer.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…36 Previous studies have shown that health-related outcomes, including chronic disease management and survival, are better when primary care is integrated as part of the care team. 37-41 In our study, it was encouraging that primary care was included in the clinical MTS for almost 74% of cancer patients. We also identified 16.7% lower incidence of high-complexity MTS care among patients with colorectal cancer compared with patients with breast cancer.…”
Section: Discussionmentioning
confidence: 78%
“…36 Previous studies have shown that health-related outcomes, including chronic disease management and survival, are better when primary care is integrated as part of the care team. [37][38][39][40][41] In our study, it was encouraging that primary care was included in the Abbreviation: MTS, multiteam system. a Clinician specialty represents the component team in which the clinician practices daily.…”
Section: Discussionmentioning
confidence: 85%
“…The study protocol, including recruitment, procedures, and data abstraction, is described in detail elsewhere. 32,33 Briefly, eligible participants were identified by the New Jersey State Cancer Registry from 10 New Jersey counties and once recruited were contacted by the study team to schedule an in-person interview. Written informed consent was collected at the time of interview along with releases of medical and pharmacy records and contact information for all clinicians seen 12 months prior to cancer diagnosis through the interview date, which occurred approximately 9-12 months after diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Twelve studies (92%) occurred during active treatment and 5 studies (38%) during survivorship (posttreatment). All U.S. studies explicitly stated that racial or ethnic minorities were included, [23][24][25][26][27][28][29][30] ranging from 20% to 100% of the study population. Four studies focused on populations that experience health and healthcare disparities, specifically Hispanic and Black cancer survivors.…”
Section: Characteristics Of the Studies And Study Populationsmentioning
confidence: 99%